AUTHENTICATION OF GRAPE SEED FACE OIL USING FTIR SPECTROSCOPY COMBINED WITH CHEMOMETRICS TECHNIQUES - PRAYOGA, ANDI; WINDARSIH, ANJAR; APRIYANA, WURI; RISWANTO, FLORENTINUS DIKA OCTA; ISTYASTONO, ENADE PERDANA (International Journal of Applied Pharmaceutics, 2024)
Objective: This research aims to authenticate grape seed oil products using FTIR spectroscopy combined with chemometric methods. Methods: In the initial stage, exploratory data analysis was carried out by applying the main components with the Principal Component Analysis (PCA) model. Second derivative spectra resulting from preprocessing of the original spectra are used to create multivariate Principal Component Regression (PCR) and Partial Least Squares (PLS) calibration models. The second derivative spectra of Grape Seed Oil (GO), Olive Oil (OO), and the binary mixture GO+OO are utilized to generate a sparse partial least squares-discriminant analysis (SPLS-DA) model. Results: The PCA model was successfully obtained with visualization that depicted a total of 93.8% in the first and second dimensions. Multivariate calibration produced the best model in PLS with second derivative spectra for both GO and OO. PLS model for GO resulted the value of Rcal2, RCV2, Rval2, RMSEC, RMSECV, and RMSEP of 0.998, 0.992, 0.982, 0.700, 1.557, and 2.331, respectively. The SPLS-DA model was successfully built and discriminated with AUC-ROC values of 1.000, 1.000, and 0.994 for GO, OO, and GO+OO, respectively. Conclusion: Authentication of grape seed face oil can be undertaken using FTIR spectroscopic methods and chemometric techniques, which can produce high sensitivity and specificity values.